STUDI NILAI RESITENSI ELEKTRODA PENTANAHAN MENGGUNAKAN METODE TIGA KUTUB PADA KONDISI TANAH BERBEDA - Kamil Amali, Lanto Mohamad; Mento, Isnain Sarjan; Salim, Sardi; Tolago, Ade Irawati; Ntobuo, Nova Elysia; Utama, Komang Arya (Journal Of Renewable Energy Engineering, 2024)
The grounding system serves as a safe path for electrical current to flow to the ground, which is important in preventing the risk of equipment damage and safety hazards. One of the critical parameters in this system is the resistance of the ground electrode, which can be measured using the three-point method. Based on PUIL 2000, the recommended grounding resistance value for electrical installations must be less than 5 ohms so that the system can work optimally and safely. The three-pole method is known to be accurate because it minimizes the influence of the environment around the electrode. However, factors such as soil type, humidity, and mineral content greatly influence the resistance of the ground electrode. Therefore, this study aims to evaluate the resistance of grounding electrodes in various types of soil, such as clay, swamp soil, damp sandy soil, dry soil, and rocky soil. Research results: The best grounding electrode resistance values ​​were obtained in clay and moist sandy soil (coastal). Meanwhile, the resistance value of the ground electrode for dry soil, rocky soil, and swamp soil does not meet the standard of ≤ 5 ohms. The factors that cause the resistance value of the ground electrode not to meet the standard are because in swampy soil the soil is dominated by insulating organic material and low content of conductive minerals. Also, moisture imbalance, electrode corrosion, and less-than-optimal electrode installation contribute. At the same time, dry soil and rocky soil are characterized by having a high level of resistivity due to low water and mineral content and a texture that does not support optimal electrical conductivity where field measurement results are not yet available. Meets the standard ≤ 5 Ω